2018
DOI: 10.1101/409128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial network state scales mtDNA genetic dynamics

Abstract: Mitochondrial DNA (mtDNA) mutations cause severe congenital diseases but may also be associated with healthy aging. MtDNA is stochastically replicated and degraded, and exists within organelles which undergo dynamic fusion and fission. The role of the resulting mitochondrial networks in the time evolution of the cellular proportion of mutated mtDNA molecules (heteroplasmy), and cell-to-cell variability in heteroplasmy (heteroplasmy variance), remains incompletely understood. Heteroplasmy variance is particular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 92 publications
(203 reference statements)
0
31
0
Order By: Relevance
“…Previous work in plants, where mtDNA recombination produces diverse cellular mtDNA admixtures of potentially different selfishnesses, has shown that multilevel intra- or intercellular selection provides a way of combatting selfish proliferation ( 36 ). The pronounced role for mitochondrial dynamics in imposing intra-cellular quality control ( 30 ), captured by many of these models ( 50–54 , 75 ), suggests that tissue-specific mitochondrial dynamics may play an important role in this multilevel selection and mitigation of selfish proliferation ( 32 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in plants, where mtDNA recombination produces diverse cellular mtDNA admixtures of potentially different selfishnesses, has shown that multilevel intra- or intercellular selection provides a way of combatting selfish proliferation ( 36 ). The pronounced role for mitochondrial dynamics in imposing intra-cellular quality control ( 30 ), captured by many of these models ( 50–54 , 75 ), suggests that tissue-specific mitochondrial dynamics may play an important role in this multilevel selection and mitigation of selfish proliferation ( 32 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial network fragmentation is intimately involved in the mechanisms of mitophagy and may also enhance the breakdown of mtDNA (2,12). Altering the levels of the endogenous regulators of mitochondrial network architecture, including Drp1, Opa1 and Mfn1/2 (11), may therefore also impose changes to the mtDNA copy number.…”
Section: Tools and Techniques For Perturbing Mtdna Copy Numbermentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) encodes a variety of proteins, peptides, transfer RNAs and ribosomal RNAs that support the functions of mitochondria, and is thereby central to numerous physiological and pathophysiological processes including development, disease and ageing (1). Both the number of mtDNAs in a cell (mtDNA copy number) and the sequences of mtDNAs are important phenotypic determinants (2). Mutations of mtDNA can cause a spectrum of mitochondrial diseases where the clinical expression depends on the specific mutation and the degree of heteroplasmy (the proportion of mutated mtDNA in a single cell) between wild-type and mutant mtDNA (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work establishes that mitochondrial deletions can expand in muscle fibres without a replicative advantage and, surprisingly, even if mutants are preferentially eliminated from the system. Despite being subject to higher rates of mitophagy -something that finds experimental support [36,37,38,39,40,41] -mutants can come to dominate zones of the fibres. We also predict that the expansion of deletions takes place through a travelling wave of mutants propagating in the muscle fibres.…”
Section: Introductionmentioning
confidence: 99%